'Being in Being': Contesting the Ontopolitics of Indigeneity. Issue 3 (3rd April 2018) - Chandler, David; Reid, Julian
Abstract: This article critiques the shift towards valorizing indigeneity in western thought and contemporary practice. This shift in approach to indigenous ways of knowing and being, historically derided under conditions of colonialism, is a reflection of the "ontological turn" in anthropology. Rather than seeing indigenous peoples as having an inferior or different understanding of the world to a modernist one, the ontological turn suggests that their importance lies in the fact that they constitute different worlds and "world" in a performatively different way. The radical promise this view holds is that a different world already exists in potentia, the access to which is a question of ontology—of being differently: 'being in being' rather than thinking, acting and world-making as if we were transcendent or "possessive" modern subjects. We argue that the ontopolitical arguments for the superiority of indigenous ways of being should not be seen as radical or emancipatory resistances to modernist or colonial epistemological and ontological legacies but rather as a new form of neoliberal governmentality, cynically manipulating critical, postcolonial and ecological sensibilities for its own ends. Thus, rather than "provincializing" dominant western hegemonic practices, such discourses of indigeneity extend them, instituting new forms of governing through calls for adaptation and resilience.